Temporary internment camp in Alytus in 1941 june-july - Lučinskas , Gintaras (Genocidas ir rezistencija, 2018)
After the Germans occupied Alytus, the Germans set up a temporary internment camp on the square used for horse riding by the uhlans next to the former Garrison Church (now St. Casimir Church). The aim of this article is to convey the atmosphere of the time, based on memoirs and documents, and to describe the people who were imprisoned there.
Keywords: Lithuania; german occupation; soviet occupation; Second World War